Anemia in elderly patients with chronic kidney disease (Research, Society and Development, 2024)
Anemia is quite common in elderly individuals with Chronic Kidney Disease (CKD) and becomes more recurrent in the advanced stage of the disease, which directly impacts the quality of life of this population. The objective of this study is to analyze the causes that relate anemia in elderly individuals with chronic kidney disease, investigating the pathophysiological mechanisms that contribute to the progression of this clinical condition. The research methodology applied in this work was an narrative review of articles, books, journals and others published between 2013 and 2023 in the following databases: Google Scholar, PubMed, Scientific Electronic Library Online (Scielo), Semantic Scholar, Academia de Ciência e Tecnologia, Biblioteca Virtual em Saúde (BVS periodicals), Ministério da Saúde (MS), Minha Biblioteca, MedLine and CAPES periodicals, using the keywords “anemia in elderly individuals”, “anemia of chronic kidney disease” and “elderly individuals with chronic kidney disease”. Twelve thematically relevant articles were chosen for discussion of the research results, which showed existing connections between CKD and the prevalence of anemia in elderly patients. The study revealed that as a result of inflammation caused by renal dysfunction, the chronic inflammatory process triggers increased production of the cytokine hepcidin, deregulating iron metabolism, which reduces its availability, resulting in restricted iron erythropoiesis and subsequent anemia. It is concluded that due to recurrent inflammation, oxidative stress and low iron availability, aging and pathogenic conditions acquired throughout life contribute to the development of Anemia of Chronic Disease (ACD) associated with CKD in the elderly.